The Authority of Sub-District Heads in Revoking Land Rights for Personal Interests: Between Legality and Justice - Tambunan, Rico J.R.; Safa’at, Rachmad; Permadi, Iwan; Sulistyarini, Rachmi (Magister of Law, Faculty of Law, University of Mataram, 2025)
After the enactment of Law Number 22 of 1999 concerning Regional Government, currently the authority of the sub-district head as a regional head has previously been attributive and is now delegative. the aim of this research is about how is the legality of the sub-district head’s authority to release land rights for private interests. The research method used is normative juridical. The research results showed that the legality of the sub-district head’s authority to release land rights for private interests is not fulfilled. This is because there is not a single clause that states that the sub-district head can sign documents releasing land rights after the enactment of Law Number 22 of 1999 concerning Regional Government, which currently has the authority of the sub-district head as a regional head from previously being attributive and now being delegative, so that the Letter of Relinquishment of Land Rights made and signed by the District Head regarding the location of the land in question, cannot be used as a formal requirement for registration of land rights at the Land Office. Based on the applicable legal provisions, the deed of releasing land rights for private purposes should be made by a Notary. An authentic deed provides more legal certainty so as to cause justice for the party who relinquishes its rights/owner as well as for the next prospective applicant. Statement of Relinquishment of Land Rights signed by the Subdistrict of Cileungsi declared invalid / null and void.